Tinjauan Kriminologi Tindak Pidana Pembunuhan Berencana Di Wilayah Hukum Polres Karawang (Studi Putusan Nomor 155/Pid.B/2022/pn. kWG) - Srihastuti, Rika; Priyana, Puti (Jurnal Ilmiah Wahana Pendidikan, 2024)
Premeditated murder is an act committed by a person or persons which results in the loss of the lives of other people by way of unlawful means and is carried out with a premeditated plan. Related to premeditated murder is regulated in Article 340 of the Criminal Code (KUHP). In this study, the authors used a juridical-empirical research method, namely according to an empirical approach, knowledge is based on facts obtained from research and observations. The problem factors in this study are what are the factors that cause premeditated murder in the jurisdiction of the Karawang Police in terms of criminology. The results of this study can be concluded, that the cause of the crime of premeditated murder is the main factor is an affair, and other supporting factors are low morale, low education, and low economic and environmental factors. Keywords: Crime, Premeditated Murder, Criminology